2012
DOI: 10.1002/cpe.2922
|View full text |Cite
|
Sign up to set email alerts
|

MyExperimentalScience, extending the ‘workflow’

Abstract: SUMMARYScience, especially experimental science, has always depended on the careful capture of plans, actions, raw and processed data and conclusions. With scientific research now so inextricably dependent on computers, the use of an electronic laboratory notebook (ELN) is almost essential. The meticulous notebooks of Michael Faraday and other scientists of his era remain as role models for the recording that is necessary, but they cannot provide the essential support for discussion, sharing, collaboration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…As such, they are potentially very useful objects to share between researchers working with similar procedures and protocols. We have implemented a link [37] with myExperiment [29] so that we can export the XML description, together with authorship details and a representative image of the template, from the LabTrove e-Notebook to myExperiment. From there, other users can be share the template or import it and use it in their own LabTrove notebook.…”
Section: Discussionmentioning
confidence: 99%
“…As such, they are potentially very useful objects to share between researchers working with similar procedures and protocols. We have implemented a link [37] with myExperiment [29] so that we can export the XML description, together with authorship details and a representative image of the template, from the LabTrove e-Notebook to myExperiment. From there, other users can be share the template or import it and use it in their own LabTrove notebook.…”
Section: Discussionmentioning
confidence: 99%
“…130 The MyExperimentalScience project is an interesting integration of ELN and workflow that links LabTrove with myExperiment, thereby making LabTrove templates, which are preformed posts that are in effect represent single steps in a workflow, available for discovery and reuse. 131 The Semantic Web…”
Section: Collaboration and Sharingmentioning
confidence: 99%
“…Some academic laboratories have developed surrogate ELNs by adapting software that were originally not intended for data recording. Examples include the use of Evernote, Googledocs, Microsoft OneNote, and web blogs as ELNs [ 13 16 ]. In addition, the following studies on inclusion of ELN in teaching laboratories have been reported in the literature: An ELN based on the Sakai software was used in an inquiry-based biochemistry teaching laboratory course [ 17 ], and the Pebblepad ePortfolio system was used as ELN in a biochemistry and molecular biology lab course [ 18 ].…”
Section: Introductionmentioning
confidence: 99%